Business And Its Application In Information Technology As Well As Good Communication - M Umar Maya Putra; Syafrida Damanik; M Saleh Malawat (Institute of Computer Science (IOCS), 2022)
This paper is a concept of business and information technology (IT) training in facing the progress of transformation of communication for college students in Management Computer Informatics (MCI) Royal Kisaran, Asahan Regency. Through this program, it is expected that they knew the importance of business in legal concept based on the improvement of IT. The method used is experiential learning method and the concept of literature study about business and IT. The delivery in the form of lectures, group discussions, games so that people can participate actively through the Focus Group Discussion (FGD). In the training presented the material: Concept of information technology (IT) training in facing the progress of transformation of communication. After the FGD are conducted, it is found that the participants are quite responsive and enthusiastic in following the training materials, as evidenced, there are many questions asked by the participants. By improving their knowledge and IT are quite good then they are going to improve the real fact through academic assistance with the motivation